Silencing of HuR Inhibits Osteosarcoma Cell Epithelial-Mesenchymal Transition via AGO2 in Association With Long Non-Coding RNA XIST - Liu, Yongming; Zhang, Yuan; Zhang, Jinxue; Ma, Jingchang; Xu, Xuexue; Wang, Yuling; Zhou, Ziqing; Jiang, Dongxu; Shen, Shen; Ding, Yong; Zhou, Yong; Zhuang, Ran (Frontiers in Oncology, 2021)
Background: Osteosarcoma (OS) is a highly malignant and aggressive bone tumor. This study was performed to explore the mechanisms of HuR (human antigen R) in the progression of OS. Methods: HuR expression levels in OS tissues and cells were detected by immunohistochemistry and western blotting. HuR siRNA was transfected into SJSA-1 OS cells to downregulate HuR expression, and then cell proliferation, migration, and epithelial-mesenchymal transition (EMT) were evaluated. RNA immunoprecipitation was performed to determine the association of the long non-coding RNA (lncRNA) XIST and argonaute RISC catalytic component (AGO) 2 with HuR. Fluorescence in situ hybridization analysis was performed to detect the expression of lncRNA XIST. Western blotting and immunofluorescence assays were performed to observe AGO2 expression after HuR or/and lncRNA XIST knockdown. Results: Knockdown of HuR repressed OS cell migration and EMT. AGO2 was identified as a target of HuR and silencing of HuR decreased AGO2 expression. The lncRNA XIST was associated with HuR-mediated AGO2 suppression. Moreover, knockdown of AGO2 significantly inhibited cell proliferation, migration, and EMT in OS. Conclusion: Our findings indicate that HuR knockdown suppresses OS cell EMT by regulating lncRNA XIST/AGO2 signaling.